The challenge of fundamentalism : political Islam and the new world disorder - Tibi, Bassam (University of California Press, 2002)
A text which suggests that Islamic fundamentalism is a result of Islam's confrontation with modernity. The author provides an analysis of the politicization of religion and, as an alternative to fundamentalism, he proposes a compact based on secular democr.
Originally published: 1998.
Keywords: Islam and politics.; Islamic fundamentalism.; Islam -- 20th century.; Islam -- 21st century.; Islam -- 1800-; Intégrisme islamique.; Islam -- Histoire -- 20e siècle.; Islam -- Histoire -- 21e siècle.; 11.84 Islam: other.; 89.29 political ideologies: other.; RELIGION / Islam / General; Islam; Islam and politics; Islamic fundamentalism; Islam.; Fundamentalisme.; Modernité.; Ordre mondial.; Politique mondiale.; Since 1800